Undifferentiated endometrial carcinoma: a National Cancer Database analysis of prognostic factors and treatment outcomes. Issue 7 (September 2019) - AlHilli, Mariam; Elson, Paul; Rybicki, Lisa; Amarnath, Sudha; Yang, Bin; Michener, Chad M; Rose, Peter G
Abstract : Background: Undifferentiated endometrioid endometrial carcinoma of the uterus is a rare, highly aggressive, and under-recognized subtype of endometrial cancer. Objective: This study evaluates survival, prognostic factors for survival, and treatment outcomes associated with undifferentiated endometrial cancer. Methods: The National Cancer Database was queried to identify patients with undifferentiated endometrial cancer who underwent definitive primary surgical treatment. Patients with all other histologic subtypes or incomplete treatment data were excluded. Univariable and multivariable Cox proportional hazards analyses were used to determine independent prognostic factors for survival. Points for each prognostic factor were assigned from regression coefficients in the final multivariable model and summed for a total score. Recursive partitioning analysis was used to determine cut-offs in the score to identify unique prognostic groups. Results: Among 349 404 women diagnosed with endometrial cancer from 2004 to 2013, 3994 (1.1%) met the criteria for diagnosis of undifferentiated endometrial cancer and 3486 had survival data. Median age at diagnosis was 65 years (interquartile range (IQR) 57–74) and 58% of patients had early stage disease. Median interval from diagnosis to surgery was 3.7 weeks (IQR 2.0–5.7). Five year overall survival was 57% (standard error (SE) 1%). Stage was the strongest predictor of survival, with a 15–20% decrement in 5 year survival for each advance in stage. Stage, age, race, and presence of comorbidities were independent predictors of survival and were used to categorize patients into five prognostic groups. Adjuvant therapy was associated with improved survival across most disease stages and prognostic groups. Multimodal adjuvant therapy was superior to unimodal treatment particularly in advanced stage unfavorable and very unfavorable groups. Conclusion: In women with undifferentiated endometrial cancer, survival is primarily driven by stage. Despite the poor overall prognosis of undifferentiated endometrial cancer, multimodal adjuvant therapy is a key component of treatment.